A low mutual coupling design of UWB array - Kasi B.; Jalil Y.E.; Chakrabarty C.K. (Institute of Electrical and Electronics Engineers Inc., 2023)
Antenna arrays; Antenna feeders; Energy gap; Microstrip antennas; Monopole antennas; Slot antennas; Electromagnetic band gaps; isolation; Microstrip fed; Mutual coupling; Planar antenna arrays; Ultra-wideband (UWB)